القانون الدولي، وإسرائيل النووية - زينب, سعد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The appendance of nuclear weapon formed a coup center in the evolution of the modern history of this weapon. A weapon of mass destruction, whichdid not change the characteristics of military actions as well as the art of leadership of the war and world peace. The principle of self – restraint, one of the most important concepts of strategic nuclear idioms. The strategy of the two superpowers during the "cold war" identified the possession of the conditions for restraint in relations between these two countries. The theory of self-restraint led to attempts to stay away of using the weapon of mass destruction. Despite of this the appendance of the idea of the possibility to usethis weapon in order to prevent the other party to use it. The determination of the role and importance of the "unclear factor" in the middle east in general and Israel's foreign policy strategy in specific proceeding from this the show of the mutual relationsbetween the forms of the principles of Israeli strategy to create conditions of war "traditional and nuclear" in the Middle East. International and national importance. Where the future of the nuclear weapons in the middle east and the serious progress that has happened as a result of the change in the The future of the nuclear weapons in the Middle East and the serious progress that has happened as a result of the change in the political leadership in the region and which is the result of the deep changes in the system of international changes reflected on the process of the formation and implementations of policy, military strategy for the region. if the nuclear weapons exist at the Arabs this could accelerate the process of reaching a just and comprehensive peace in the Middle East. After that it is possible to talk about the establishment of zones free of nuclear weapon. The analysis of Israel nuclear weapon which was formed in conditions of solving the Middle East crisis, the possibility of changing the position of Israel's nuclear practicality possible "nuclear reality" will present in the system of international relations in the Middle East. إنّ ظهور السلاح النووي، شكل مركز انقلاب، في تطور التاريخ المعاصر. هذا السلاح، سلاح الدمار الشامل، الذي لم يغير صفات الأعمال العسكرية بل، وكذلك فن قيادة الحرب، والسلم العالميين. مبدأ ضبط النفس – واحد من أهم مفاهيم مصطلحات الاستراتيجية النووية، استراتيجية الدولتين العظميين في فترة "الحرب الباردة" حددت امتلاك الظروف "لضبط النفس في العلاقات بين هاتين الدولتين. نظرية "ضبط النفس" أدت إلى محاولات الابتعاد عن استخدام سلاح الإبادة الشاملة، ومع هذا فإن ظهور فكرة إمكانية استخدام هذا السلاح بهدف منع استخدامه من الطرف الآخر. ويلعب العامل النووي دوراً هاماً في تشكيل الظروف السياسية في الشرق الأوسط عموماً، واستراتيجية السياسة الخارجية الإسرائيلية خصوصاً. وانطلاقاً من هذا، فإن إظهار الصلات المتبادلة بين أشكال مبادئ الاستراتيجية الإسرائيلية، لتكوين ظروف نشوب حرب "تقليدية" و"نووية" في الشرق الأوسط أهمية إقليمية وعالمية، حيث إن مستقبل السلاح النووي في الشرق الأوسط، والتقدم الجدي الذي حصل نتيجة التغير في القيادة السياسية في المنطقة، والحاصل نتيجة التغيرات العميقة في نظم العلاقات الدولية، انعكس ذلك على عملية تشكيل وتطبيق استراتيجية السياسة العسكرية لدول المنطقة. لو كان السلاح النووي موجوداً عند العرب، لكان بالإمكان تسريع عملية الوصول إلى السلام العادل والشامل في الشرق الأوسط، بعد ذلك من الممكن الحديث عن إقامة مناطق خالية من السلاح النووي. إن تحليل "السياسة النووية الإسرائيلية" التي تشكلت في ظروف حل أزمة الشرق الأوسط، إمكانية تغيير موقف إسرائيل النووي عملياً غير ممكن، "الواقع النووي" سيحضر في نظام العلاقات الدولية في منطقة الشرق الأوسط".